The Apologetics of Evil : The Case of Iago - Raatzsch, Richard (Book collections on Project MUSE., 2009)
This book is a concise philosophical meditation on Iago and the nature of evil, through the exploration of the enduring puzzle found in Shakespeare's Othello. What drives Iago to orchestrate Othello's downfall? Instead of treating Iago's lack of motive as the play's greatest weakness, The Apologetics of Evil shows how this absence of motive is the play's greatest strength. Richard Raatzsch determines that Iago does not seek a particular end or revenge for a discrete wrong; instead, Iago is governed by a passion for intriguing in itself. Raatzsch explains that this passion is a pathological ver.